Hydrotreating and hydrodemetalation of raw jatropha oil using mesoporous Ni-Mo/γ-Al2O3 catalyst. (15th October 2022) - Pal, Neeraj; Verma, Vikas; Khan, Azeem; Mishra, Ankit; Anand, Mohit; Venkata Pramod, Chodimella; Akhtar Farooqui, Saleem; Kumar Sinha, Anil
Highlights: Hydrotreating and hydrodemetalation of jatropha oil using Ni-Mo/γ-Al2 O3 catalyst. Green diesel production with simultaneous hydrodemetalation using Ni-Mo/γ-Al2 O3 . Maximum hydrodemetalation of 83.4% was achieved at 250 °C temperature. Higher temperature and low H2 /feed ratio improve diesel selectivity (91.3%). Maximum conversion (97.2%) with 68.4% of hydrodemetalation noticed at 420 °C. Abstract: During the hydroprocessing reactions, one of the major reason for the deactivation of the catalyst and pore blockage of the active sites of the catalyst is the metals present in feed. It is extremely important to remove the metals to improve catalyst aging, therefore a heterogeneous mesoporous Ni-Mo/γ-Al2 O3 catalyst was used for hydrodemetalation (HDM) of untreated non-edible raw jatropha oil (RJO). The results show that the highest HDM of 83.4% was achieved at 250 °C temperature, 5 h −1 LHSV, and 666 (V/V) H2 /feed ratio. The highest RJO conversion (97.2%) was obtained at 420 °C temperature with simultaneously 68.4% HDM. Lower temperature (250 °C) was more favourable for HDM due to minimum C–C cracking reactions than high temperature (420 °C), which favours more C–C/C-O bond cleavage. The catalyst shows prolonged activity up to 162 h, as compared to reported catalysts. TGA study of the spent catalyst indicates a 7.8 wt% coke deposition, complemented by TEM results. 13 C solid-state NMR revealed saturated hydrocarbon-type compounds deposited over the catalyst supported by FTIR analysis. The physicochemical properties of bimetallic Ni-Mo catalyst show suitable surface area and pore diameter for the diffusion of triglycerides over the surface and pores of the catalyst. The catalyst showed the potential for HDM of RJO at a lower temperature of 250 °C and green diesel (C15-C18) production at a higher temperature of 420 °C.